2002
DOI: 10.1212/01.wnl.0000035636.83680.c6
|View full text |Cite
|
Sign up to set email alerts
|

Driving safety in Parkinson’s disease

Abstract: In this study, 39 patients with PD and 25 control subjects without neurologic disease completed testing in a driving simulator. PD patients had more total collisions on the driving simulator than control subjects (t = -3.7, p < 0.01). In PD patients, collisions were associated with Hoehn and Yahr stage (chi(2) = 12.4, p = 0.006) and correlated with Unified Parkinson's Disease Rating Scale score (r = 0.5, p < 0.01).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
89
0
2

Year Published

2005
2005
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 83 publications
(99 citation statements)
references
References 2 publications
8
89
0
2
Order By: Relevance
“…Parkinson's disease has previously been found as a 14 major factor of driving cessation 49 and as a non-significant factor in crashes. 50 52 The high rate of driving cessation after a stroke was consistent with other studies. 11,12,49,53 Stroke survivors seemed to limit their driving exposure and/or rely on others for transportation, suggesting selfregulated behavior.…”
Section: Factors Associated With Driving Cessation Onlysupporting
confidence: 89%
“…Parkinson's disease has previously been found as a 14 major factor of driving cessation 49 and as a non-significant factor in crashes. 50 52 The high rate of driving cessation after a stroke was consistent with other studies. 11,12,49,53 Stroke survivors seemed to limit their driving exposure and/or rely on others for transportation, suggesting selfregulated behavior.…”
Section: Factors Associated With Driving Cessation Onlysupporting
confidence: 89%
“…The review yielded 9 Class III studies. 6,9,14,[35][36][37][38][39][40] Conclusion. From the 9 Class III studies, we concluded that cognitive abilities may deteriorate even in mild to moderate stages of PD.…”
Section: Rating Article By Classmentioning
confidence: 96%
“…14 Disease severity (H&Y) was associated with worse simulated driving performance. 35 The use of external cues may help improve skills related to driving. 39 Recommendations.…”
Section: Rating Article By Classmentioning
confidence: 99%
See 1 more Smart Citation
“…Dubinsky and colleagues (Dubinsky et al, 1991) found that although self-reported accidents were more common among PD patients with moderately severe disease (Hoehn & Yahr III) compared to mild disease (Hoehn & Yahr I) or elderly controls, disease severity scales did not reliably predict inability to drive. However, Zesiewicz and colleagues (Zesiewicz et al, 2002) found that crash frequency in individuals with PD was in fact related both to Hoehn & Yahr (H&Y) stage (Hoehn & Yahr, 1967) and to Unified Parkinson Disease Rating Scale (UPDRS) motor score (Fahn et al, 1987). Consistent with these latter findings, Madeley et al (1990) found a correlation between PD severity on Webster's rating scale (a 10 item scale of Parkinsonian motor symptoms) and simulated driving reaction time and steering accuracy, and Radford et al (2004) found that the Webster's rating scale, but not cognitive measures, differentiated between safe and unsafe driving on a road test.…”
Section: Introductionmentioning
confidence: 99%